The Illinois Detective Agency : the case of the missing children [large type] - Wolfe, Ethan J. (Wheeler large print western series., 2023)
"After the murder of Illinois Detective Agency founder Charles Porter by a mysterious criminal named King Valdez, the team comes together with just one thought on its mind: find Valdez and bring him to justice. King Valdez is kidnapping children and selling them into slavery around the world. His operation is large and well organized and well financed. James Duffy assumes control of the agency and works closely with the Justice Department to find Valdez. Agents Jack Cavill, Joseph Goodluck, Quill, Harvey, Holt, and newcomer Mr. Sato round out the team. A countrywide investigation uncovers Valdez's method of operation. He uses hired privateer ships to smuggle the kidnapped children out of the country. A widespread manhunt leads to the capture of several privateer captains, who, in exchange for lenient sentences, give up Valdez. Valdez is hiding in the Sonoran Desert and Duffy, Cavill, Goodluck, and Sato make the journey across the desert to find him"--